Fluazuron-induced morphophysiological changes in the cuticle formation and midgut of Rhipicephalus sanguineus Latreille, 1806 (Acari: Ixodidae) nymphs - De Oliveira, Patrícia Rosa [UNESP]; Calligaris, Izabela Braggião [UNESP]; Roma, Gislaine Cristina [UNESP]; Bechara, Gervásio Henrique [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (My University, 2013)
The present study demonstrated the effects of the arthropod growth regulator, fluazuron (Acatak®), in the formation of the integument and digestive processes of Rhipicephalus sanguineus nymphs fed on rabbits treated with different doses of this chemical acaricide. For this, three different doses of fluazuron (20, 40, or 80 mg/kg) were applied pour on to the hosts (groups II, III, and IV), as well as distilled water to the control group. On the first day after treatment (24 h), the hosts were artificially infested with R. sanguineus nymphs. After full engorgement (7 days), the nymphs were removed, placed on labeled Petri dishes, and kept in biochemical oxygen demand incubator for 7 days. The engorged nymphs were then taken for morphological, histochemical, and histological analyses. The results showed the occurrence of cytological, morphohistological, and histochemical alterations in the integument and midgut of nymphs from all the different treated groups. These alterations occurred at cuticular level in the subdivisions of the cuticle, related to the size of the digestive cells, amount of accumulated blood elements, and digestive residues, as well as the presence of vacuoles in the cytoplasm of the digestive cells. Thus, this study demonstrated that fluazuron acts on the integument and midgut cells of R. sanguineus nymphs fed on treated rabbits and pointed out the possibility of the use of this chemical - which is more specific, less toxic, and less harmful to the environment and nontarget organisms - in the control of R. sanguineus, at least in the nymphal stage of its biological cycle. © 2012 Springer-Verlag.
Keywords: fluazuron; animal experiment; animal model; animal tissue; biochemical oxygen demand; cell shape; cell size; cell vacuole; cellular distribution; controlled study; cuticle; growth regulation; histochemistry; host parasite interaction; midgut; nonhuman; nymph; parasite control; priority journal; Rhipicephalus sanguineus; tick infestation; tissue characterization; Acaricides; Animals; Gastrointestinal Tract; Histocytochemistry; Integumentary System; Microscopy; Nymph; Phenylurea Compounds; Rabbits; Acari; Arthropoda; Ixodidae; Oryctolagus cuniculus